Indus water treaty regime - Arora, R. K. (New Delhi, 2007)
Book Summary of The Indus Water Treaty Regime The Indus treaty is a complex instrument. Its basic approach was to increase the amount of water available to India and Pakistan. It is to apportion the water resources of the Indus equitably between them. The conclusion of the treaty in 1960 was a remarkable achievement. Aim of this book is to prepare for our readers a comprehensive and uptodate account of the dispute as well as the persent treaty regime applicable to the waters of the Indus Rivers System. About Author : Dr.R.K.Arora is a widely travelled and well read scholar and thinker. He has thirty six year of experience of teaching and research. He has participated in the national and international conferences in India and abroad. A member of Board of Studies of several universities. Dr. Arora is an established author. Contents : Preface The Indus River Development of Institutional Framework for the Management of Transboundary Water Resources Indus Water Treaty Options for Resolving The Conflict Water and Human Security Water Rationality Water Resources Pakistan View Point Appendices Index
Keywords: Water